Analisis Promosi dan Harga terhadap Keputusan Pembelian melalui Brand Image pada Toko Kopi Tuku di Kota Bekasi - Gita Rezda Andiwa; M. Fadhli Nursal; Haryudi Anas (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of promotion and price on purchase decisions through Brand Image as a mediating variable among consumers of Toko Kopi Tuku in Bekasi City. A quantitative approach was applied using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with data collected from 140 respondents selected through purposive sampling and processed using SmartPLS 4.0. The results show that promotion and price each have a positive and significant effect on Brand Image, with promotion contributing the strongest effect. Promotion, price, and Brand Image also have a positive and significant direct effect on purchase decisions. Furthermore, Brand Image partially mediates the effect of both promotion and price on purchase decisions. The model explains 70.3% of the variance in Brand Image and 79.2% of the variance in purchase decisions, both showing high predictive relevance (Q² > 0.5). These findings indicate that local coffee shop brands such as Toko Kopi Tuku need to maintain consistent promotional activity and fair pricing to strengthen Brand Image and encourage consumer purchase decisions.